Functional outcomes and tracheostomy dependence following salvage oropharyngeal surgery. (February 2021) - Heft Neal, Molly E.; Gao, Rebecca W.; Brennan, Julia R.; Haring, Catherine T.; Chinn, Steven B.; Shuman, Andrew G.; Casper, Keith A.; Malloy, Kelly M.; Stucken, Chaz L.; Mclean, Scott A.; Chad Brenner, J.; Lyden, Teresa; et al.
Highlights: Increasing HPV mediated disease results in increasing number of patients requiring oropharyngectomy after prior radiation. Functional outcomes are an important facet of shared decision making for treatment algorithms. Pre-operative clinical factors can help to predict post-operative functional outcomes.